Abroad in Japan : ten years in the Land of the Rising Sun - Broad, Chris, ....- (London : Transworld Publishers Penguin, 2024)
When Englishman Chris Broad landed in a rural village in northern Japan he wondered if he'd made a huge mistake. With no knowledge of the language and zero teaching experience, was he about to be the most quickly fired English teacher in Japan's history? Abroad in Japan charts a decade of living in a foreign land and the chaos and culture clash that came with it. Packed with hilarious and fascinating stories, this book seeks out to unravel one the world's most complex cultures. Spanning ten years and all forty-seven prefectures, Chris takes us from the lush rice fields of the countryside to the frenetic neon-lit streets of Tokyo. With blockbuster moments such as a terrifying North Korean missile incident, a mortifying experience at a love hotel and a week spent with Japan's biggest movie star, Abroad in Japan is an extraordinary and informative journey through the Land of the Rising Sun.
Keywords: Japan